2020
DOI: 10.1002/agj2.20412
|View full text |Cite
|
Sign up to set email alerts
|

Cotton boll distribution and yield estimation using three‐dimensional point cloud data

Abstract: Node-by-node boll mapping has been used to determine the effects of several environmental and management strategies, including irrigation rate and cultivar, on cotton (Gossypium hirsutum L.) boll distribution. The advent of consumer 3D digital imaging may make rapid node-by-node mapping of greater acreage possible in the future. Effects of irrigation rate and cultivar on boll distribution were determined from line plots of node-specific boll distribution and boll accumulation estimate data and from vertical bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Stevens et al (1992) observed that wheat stubble residue decreased the number of bolls formed on nodes 5-8 on cotton plants compared to a fallow control. As noted by Bauer and Busscher (1996), changes in boll distribution on plants may negatively affect lint yields and fiber quality due to changes in source-sink relationships and indeterminate flowering that results in less time for boll fill (Dube et al, 2020;Ritchie et al, 2009). Additionally, weed pressure has previously been associated with reductions in cotton yield, likely by making bolls develop higher on the plant or later into the season (Blaise, 2006;Elms et al, 2001).…”
Section: Core Ideasmentioning
confidence: 99%
“…Stevens et al (1992) observed that wheat stubble residue decreased the number of bolls formed on nodes 5-8 on cotton plants compared to a fallow control. As noted by Bauer and Busscher (1996), changes in boll distribution on plants may negatively affect lint yields and fiber quality due to changes in source-sink relationships and indeterminate flowering that results in less time for boll fill (Dube et al, 2020;Ritchie et al, 2009). Additionally, weed pressure has previously been associated with reductions in cotton yield, likely by making bolls develop higher on the plant or later into the season (Blaise, 2006;Elms et al, 2001).…”
Section: Core Ideasmentioning
confidence: 99%
“…Many scholars have tried to develop various ground-based sensing systems. For example, images obtained by a digital camera installed on a robot platform have been used to estimate the number of cotton bolls based on the images collected by either a 3D sensor system, the estimated value of cotton bolls, or the lint obtained from the point cloud [18] . With the calculation of the number of cotton bolls in the field, accurate cotton yield predictions can be provided [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have tried to develop various ground-based sensing systems. For example, a digital camera installed on a robotic platform was used to estimate the number of cotton bolls based on images acquired by the 3D sensor system, boll estimates, or lint obtained from point clouds [ 19 ]. With the calculation of the number of cotton bolls in the field, accurate cotton yield prediction can be achieved [ 20 ].…”
Section: Introductionmentioning
confidence: 99%